Apelin-13 protects the lungs from ischemia-reperfusion injury by attenuating inflammatory and oxidative stress. (April 2021) - Xia, F; Chen, H; Jin, Z; Fu, Z
Apelin has been reported to regulate mitochondrial function in myocardial ischemia-reperfusion injury and cerebral ischemia-reperfusion injury. However, the role of apelin-13 in lung ischemia-reperfusion injury (LIRI) remains unclear. This study established an experimental rat model to evaluate the underlying mechanisms of apelin-13 on LIRI. Twenty-four rats were randomly divided to sham operation group (group SM), ischemia/reperfusion group (group IR), and apelin-13 treatment group (group APL). The effects of apelin-13 on LIRI were determined histologically using H&E staining, while the wet/dry weight ratio was used to assess lung edema caused by LIRI. Inflammatory cytokines were also detected in Bronchoalveolar lavage (BAL) fluid by ELISA. The protein expression of UCP2 and the morphological changes of mitochondria were determined by western blotting and electromicroscopy, respectively. The results demonstrated the structural damage of lung tissues and lung edema in group IR. An increased level of inflammatory cytokines including IL-1β, IL-6 and TNF-α was observed in rats with LIRI using ELISA. After that, oxidative stress and morphological damage of mitochondria were also shown in group IR. Yet, the application of apelin-13 reversed all these deleterious effects in group APL. The protective effects of apelin-13 were indicated by decreased reactive oxygen species (ROS) and elevated UCP2 expression levels in rats. In conclusion, this study revealed that apelin-13 had protective effects against LIRI via attenuating lung edema, the production of inflammatory cytokines, oxidative stress and mitochondrial dysfunction.